2013
DOI: 10.1371/journal.pone.0064379
|View full text |Cite
|
Sign up to set email alerts
|

A Modified MELD Model for Chinese Pre-ACLF and ACLF Patients and It Reveals Poor Prognosis in Pre-ACLF Patients

Abstract: Background & AimsAcute-on-chronic liver failure (ACLF) is one of the most deadly, prevalent, and costly diseases in Asia. However, no prognostic model has been developed that is based specifically on data gathered from Asian patients with ACLF. The aim of the present study was to quantify the survival time of ACLF among Asians and to develop a prognostic model to estimate the probability of death related to ACLF.MethodsWe conducted a retrospective observational cohort study to analyze clinical data from 857 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
34
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 26 publications
7
34
2
Order By: Relevance
“…Using the Cox proportional hazard model, we identified the characteristics of the majority of patients who would not immediately recover from the insults. Those patients were characterized by old age, severe hepatic damage (high MELD score) and high occurrence of HE, which was consistent with previous reports . Age as an independent risk factor in ACLF was not surprising as patients of older age usually had a higher frequency of comorbidity, longer duration of underlying disease and poor hepatic regeneration in response to acute insults.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Using the Cox proportional hazard model, we identified the characteristics of the majority of patients who would not immediately recover from the insults. Those patients were characterized by old age, severe hepatic damage (high MELD score) and high occurrence of HE, which was consistent with previous reports . Age as an independent risk factor in ACLF was not surprising as patients of older age usually had a higher frequency of comorbidity, longer duration of underlying disease and poor hepatic regeneration in response to acute insults.…”
Section: Discussionsupporting
confidence: 89%
“…Those patients were characterized by old age, severe hepatic damage (high MELD score) and high occurrence of HE, which was consistent with previous reports. 19,20 Age as an independent risk factor in ACLF was not surprising as patients of older age usually had a higher frequency of comorbidity, longer duration of underlying disease and poor hepatic regeneration in response to acute insults. Our results demonstrated that HE was another independent risk factor integrated into the MELD-sodium model.…”
Section: Discussionmentioning
confidence: 99%
“…This perhaps suggests that the ACLF by APASL includes probably a cohort of pre-ACLF patients, who not necessarily have a high immediate mortality or in whom a timely intervention prevents development of significant organ failures other than liver failure, thereby reducing the chances of mortality. Also, CLIF-SOFA score had a higher sensitivity in predicting mortality as compared to both MELD and CTP score, though some of the previous studies have found MELD score to be equally good in predicting mortality [17].…”
Section: Discussionmentioning
confidence: 72%
“…Overt ascites was diagnosed by clinical examination and ultrasonography as previously described . HE was defined as an episode of neurological and neuropsychiatric abnormality …”
Section: Methodsmentioning
confidence: 99%